Análisis de los supuestos epistemológicos y ontológicos presentes en tres investigaciones ecológicas realizadas en la laguna costera de mar chiquita sobre el poliqueto invasor Ficopomatus enigmaticus - Denegri, Guillermo Maria (2017)
In order to show the epistemological (empiricist, rationalist, racioempiricist)and ontological (individualistic, holistic, sistemist) assumptions present inecological research, which often remain implicit, this paper analyzes threeinvestigations in ecology made in the coastal lagoon of Mar Chiquita (37° 40?S,57° 23?W, Argentina (Obenat 2001; Schwindt 2001; Bruschetti, et al., 2008), froman epistemological and ontological viewpoint. Those articles assess the ecologi-cal consecuences of an invasive species, the reef forming polychaete F. enig-maticus. The disadvantages of implementing purely rationalist or empiricistepistemologies in ecological research, and the advantages of using a racioem-piricists one are shown here.